Core-crosslinking as a pathway to develop inherently antibacterial polymeric micelles - Kadayifci, Melike Seyma; Gokkaya, Damla; Topuzogullari, Murat; Isoglu, Sevil Dincer; Atabey, Tugba; Arasoglu, Tulin; Ozmen, Mehmet Murat (WILEY, 2020)
Positively charged polymeric materials have been an alternative to combat bacteria as they exhibit inherently antibacterial potency via bacteria membrane disruption. In this study, we report facile preparation of positively charged core-crosslinked polymeric micelles with inherent antibacterial properties. Spherical micelles were prepared by self-assembling of poly(4-vinylpyridine)-b-(oligoethylene glycol methyl ether methacrylate) copolymer in aqueous solution. Herein, quaternization reaction was utilized for the first time to core crosslink the micelles through the pyridine rings utilizing their hydrophobic core and thus resulting positively charged nanostructures. Dynamic light scattering (DLS) results identified that the micelles have an average hydrodynamic diameter of 114 nm with a polydispersity index ranging between 0.105 and 0.114. The electrophoretic light scattering (ELS) measurements demonstrated that the micelles have zeta potential values ranging from +38 to +63 mV. It was evident from both ELS and DLS results that the micelles in solution exhibit long-term stability as the samples were able to maintain their size and charge even after a year of storage. Further, the micelles exhibited inherently antibacterial activity against Escherichia coli and furthermore, this antibacterial efficacy was sustained over a period of 1 year. These stable core-crosslinked micelles are proposed to have great potential as antibacterial materials for long-term applications. (c) 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 48393.
Keywords: bioengineering; copolymers; crosslinking; micelles; self-assembly; QUATERNARY AMMONIUM; ANTIMICROBIAL POLYMERS; QUATERNIZATION; NANOPARTICLES; FABRICATION; Polymer Science